Critical analysis of judicial review of administrative actions in Iran - Mohammad Moghadamfard, (Penerbit Universiti Kebangsaan Malaysia, 2018)
To have a thorough insight of judicial review of administrative action in Iran it seems necessary to have a brief look at judicial review over past decades, to be more specific Shah’s regime. The system of government in Shah’s regime similar to many countries in 19th century was monarchy, but there were formal limitations on Shah’s discretion and the kingdom office was passed to him through inheritance. At that time judicial review of administrative action was left to the ordinary courts. This means that there was no special administrative court to deal with disputes between individuals and public bodies; and the system was inspired by the Anglo-Saxon system of judicial review. The inadequacy and inefficiency of the judicial review system gave rise to an increasing discontent on part of individuals at the end of Shah’s regime and eventually the Council of State Act was passed to improve judicial review and eliminate defects but this never came into practice. The Islamic Revolution in Iran heralds a dawn in the field of citizens’ rights because the governmental system is based on Islam and Democracy. Accordingly, the Administrative Justice Tribunal was established as a special administrative court for reviewing administrative actions but there are still defects in the current system which this article seeks to highlight and propose solutions. The main objective of this article is to assess how far the present system of judicial review is efficient in protecting citizens’ rights. This is a pure legal research in terms of methodology and is a qualitative one.